Influence of Strategy Formulation and Implementation on Tourist Destination Performance - Zulhikmah, Zulhikmah; Akadun, Akadun; Hafel, Muhlis (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2025)
Purpose – This study aims to examine the effect of strategy formulation and strategy implementation on improving the performance of tourist destinations, specifically Mount S in West Kutai Regency, East Kalimantan. The research investigates how strategic planning processes influence destination management and performance in an emerging tourism area. Methodology/approach – A quantitative descriptive approach was used, involving data collection through a closed questionnaire with a Likert scale. The survey targeted tourism stakeholders in West Kutai Regency, including government officials, local parliament (DPRD), community members, tourism awareness groups, managers, and tourists. Data analysis was performed using multiple linear regression with SPSS 22 software. Findings – The results reveal that both strategy formulation and strategy implementation have a positive and significant impact on the performance of Mount S tourist destination. The coefficient of determination (R²) indicates that 76.6% of the performance improvement is explained by these factors, emphasizing the importance of integrated strategy development and execution. Novelty/value – This research makes a significant contribution by exploring the dynamics of strategy formulation and implementation in a developing region of Indonesia, specifically West Kutai Regency. The study fills a gap in the existing literature by examining how these strategic processes can directly enhance the performance of emerging tourist destinations, an area that has been underexplored in the context of Indonesian tourism management.